An antioxidant stainless steel with phase transformation induced plasticity and a method of making the same
Patent Information
- Application Number
- CN202511984865.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-26
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2045-12-26
AI Technical Summary
[0003]目前使用最为广泛的不锈钢是304、316L等奥氏体不锈钢,但这些不锈钢室温下强度较低,面对工程机械部件承载、结构件抗形变等场景时,易出现性能短板,影响设备的耐用性与安全性;在能源化工高温反应、热加工等高温应用环境中,其抗氧化能力不足,表面易产生氧化腐蚀,缩短部件使用寿命,甚至影响生产流程稳定性;且这些钢的Ni含量均大于8wt.%,原材料成本较高,难以满足工业应用领域对成本的要求
1、本发明通过合理调配合金元素Ni、Mn、C、Si的含量和配比,通过调控镍当量确保合金大多数为奥氏体并保证其处于亚稳态,在室温下发生形变诱导相变,进而使得本发明所述不锈钢在室温下实现了高强度、优异塑性。同时,通过引入适量的Si,提高了合金抗氧化性能和高温强度,本发明提供的不锈钢室温下屈服强度超过350 MPa,抗拉强度超过1040MPa,断后伸长率大于50%;400℃-700℃下屈服强度、抗拉强度和断后伸长率均优于304和316L不锈钢,解决了现有304和316L不锈钢无法同时兼具较高强度与优良抗氧化性能的问题;
Smart Images

Figure CN121653536B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of stainless steel preparation technology, and in particular to an antioxidant stainless steel with phase transformation induced plasticity and its preparation method. Background Technology
[0002] Stainless steel, with its excellent corrosion resistance, good mechanical properties (covering strength, toughness and processability), and performance stability over a wide temperature range, is widely used in engineering machinery, energy and chemical industries, and is one of the key materials that are indispensable in modern production and life.
[0003] Currently, the most widely used stainless steels are austenitic stainless steels such as 304 and 316L. However, these stainless steels have low strength at room temperature, which can lead to performance shortcomings when facing load-bearing engineering machinery parts and deformation resistance of structural components, affecting the durability and safety of equipment. In high-temperature applications such as high-temperature reactions and hot processing in energy and chemical industries, their oxidation resistance is insufficient, and the surface is prone to oxidation corrosion, which shortens the service life of components and may even affect the stability of the production process. Moreover, the Ni content of these steels is greater than 8 wt.%, resulting in high raw material costs, which makes it difficult to meet the cost requirements of industrial applications.
[0004] Phase transformation induced plasticity is a method that can simultaneously improve the strength and plasticity of steel. This effect generally occurs in austenitic steel. During deformation, austenite undergoes a deformation-induced phase transformation and gradually transforms into martensite. This phase transformation process can not only significantly improve the tensile strength of the material through the high strength characteristics of martensite itself, but also provide additional plastic deformation to the material, so that the material can maintain good plasticity while maintaining ultra-high strength.
[0005] Therefore, introducing phase transformation-induced plasticity into steel to obtain a new type of phase transformation-induced plasticity anti-oxidation stainless steel with higher strength, lower production cost and excellent oxidation resistance has become an urgent problem to be solved. Summary of the Invention
[0006] The purpose of this invention is to overcome the problems in the prior art and provide a phase transformation-induced plasticity-resistant stainless steel and its preparation method.
[0007] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a phase transformation-induced plasticity-resistant oxidation-resistant stainless steel, comprising the following components by mass percentage: Cr: 16~18%, Ni: 5~7%, Mn: 2~6%, Si: 2~4%, C: 0.15~0.25%, balance Fe; The above components satisfy the following relationship: 10.3 <W(Ni)eq<13.7; in: W(Ni)eq=W(Ni)+0.6W(Mn)+0.18W(Cr)+9.69W(C)-0.11W(Si) 2 ; W(X) represents the mass percentage of element X multiplied by 100, and W(Ni)eq is the nickel equivalent.
[0008] The present invention further provides a preparation method of the oxidation-resistant stainless steel with transformation-induced plasticity, comprising the following steps: (1) Melting the components to obtain a billet; (2) Subjecting the billet to hot working and recrystallization in sequence, to obtain the oxidation-resistant stainless steel with transformation-induced plasticity.
[0009] As a preferred option, the melting conditions in step (1) are an argon atmosphere or vacuum.
[0010] As a preferred option, the temperature of the hot working in step (2) is 850~1250°C.
[0011] As a preferred option, the deformation amount of the hot working in step (2) is ≥80%.
[0012] As a preferred option, the temperature of the recrystallization in step (2) is 700~1300°C.
[0013] As a preferred option, the time of the recrystallization in step (2) is ≥3min.
[0014] The present invention provides an oxidation-resistant stainless steel with transformation-induced plasticity, comprising the following components in mass percentage: Cr: 16~18%, Ni: 5~7%, Mn: 2~6%, Si: 2~4%, C: 0.15~0.25%, with the balance being Fe; the above components satisfy the following relationship: 10.3<W(Ni)eq<13.7; wherein: W(Ni)eq=W(Ni)+0.6W(Mn)+0.18W(Cr)+9.69W(C)-0.11W(Si) 2 . In the present invention, Cr is a key element for ensuring the corrosion resistance of the alloy; however, excessively high Cr will increase the cost of the steel. Therefore, the mass percentage of Cr should be controlled at 16~18%.
[0015] In the present invention, Ni can regulate the stability of austenite in the alloy. Too low Ni will reduce the stability of austenite, resulting in a decrease in the volume fraction of austenite, so that there is not enough austenite to participate in the deformation-induced transformation process, and the elongation of the alloy is reduced; excessively high Ni will increase the stability of austenite, so that the austenite does not undergo phase transformation during the deformation process, that is, no transformation-induced plasticity is generated; at the same time, Ni will increase the cost of the alloy, therefore, the mass percentage of Ni should be controlled at 5~7%.
[0016] In this invention, Mn is an inexpensive substitute for Ni and can also regulate the stability of austenite in the alloy, keeping the stability of austenite within a reasonable range, thereby improving the elongation and strength of the alloy through deformation-induced phase transformation; however, excessive Mn will increase the difficulty of smelting and also impair the oxidation resistance of the alloy. Therefore, the mass percentage of Mn should be controlled at 2~6%.
[0017] In this invention, C is also an inexpensive alternative to Ni, which can regulate the stability of austenite in the alloy and regulate the deformation-induced phase transformation effect; however, excessive C will combine with Cr to form carbides, causing chromium-depleted areas inside the alloy and reducing corrosion resistance. At the same time, excessive C will also reduce the pitting corrosion resistance of the alloy in chloride-containing media. Therefore, the mass percentage of C should be controlled at 0.15~0.25%.
[0018] In this invention, silicon (Si) is a key element for ensuring the alloy's oxidation resistance; too low a Si content will significantly reduce the alloy's high-temperature oxidation resistance. Simultaneously, Si is also a key element for regulating austenite stability, controlling the alloy's ability to undergo transformation-induced plasticity at room temperature. Lower Si content stabilizes austenite, preventing it from undergoing a phase transformation during room temperature deformation, thus reducing the alloy's room temperature elongation. Conversely, excessive Si content leads to a large amount of ferrite in the alloy, resulting in insufficient austenite for deformation-induced phase transformation, significantly reducing the alloy's elongation. At high temperatures, Si also plays a role in solid solution strengthening, improving the alloy's high-temperature strength. Therefore, the mass percentage of Si should be controlled at 2-4%.
[0019] As can be seen from the above technical solution, compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention achieves high strength and excellent plasticity in stainless steel at room temperature by rationally adjusting the content and ratio of alloying elements Ni, Mn, C, and Si, and by controlling the nickel equivalent to ensure that the majority of the alloy is austenitic and remains in a metastable state. This allows for deformation-induced phase transformation at room temperature. Simultaneously, the introduction of an appropriate amount of Si improves the alloy's oxidation resistance and high-temperature strength. The stainless steel provided by this invention has a yield strength exceeding 350 MPa, a tensile strength exceeding 1040 MPa, and an elongation after fracture greater than 50% at room temperature. At 400℃-700℃, its yield strength, tensile strength, and elongation after fracture are all superior to those of 304 and 316L stainless steels, solving the problem that existing 304 and 316L stainless steels cannot simultaneously possess both high strength and excellent oxidation resistance. 2. The phase transformation-induced plasticity-resistant stainless steel of this invention has a low Ni content, only 5-7%, and does not contain expensive elements such as Mo and W. Furthermore, it can utilize non-high-purity raw materials containing C and Si, significantly reducing the production cost of the stainless steel. In addition, the preparation process of the phase transformation-induced plasticity-resistant stainless steel of this invention is simple and efficient, requiring only smelting, casting, hot working, and recrystallization, making it suitable for large-scale industrial production. Attached Figure Description
[0020] Figure 1 The image shows the EBSD diagrams of the antioxidant stainless steel before and after stretching in Example 1, which exhibits phase transformation-induced plasticity. Detailed Implementation
[0021] This invention provides a phase transformation-induced plasticity-resistant oxidation-resistant stainless steel, comprising the following components by mass percentage: Cr: 16~18%, Ni: 5~7%, Mn: 2~6%, Si: 2~4%, C: 0.15~0.25%, balance Fe; The above components satisfy the following relationship: 10.3 <W(Ni)eq<13.7; in: W(Ni)eq=W(Ni)+0.6W(Mn)+0.18W(Cr)+9.69W(C)-0.11W(Si) 2 ; W(X) represents the mass percentage of element X × 100, and W(Ni)eq is the nickel equivalent, which represents the sum of the mass percentages of nickel and its substitute elements multiplied by their substitution coefficients × 100.
[0022] In this invention, nickel equivalent is an expression well known to those skilled in the art. In different stainless steel systems, the calculation method of nickel equivalent is different, for example, CN119932446A, CN105200340A, "Influence of different chromium-nickel equivalent ratios on the microstructure of 2304 duplex stainless steel cold-rolled sheet".
[0023] In this invention, the mass percentage of Cr is preferably 16.5-17.5%, more preferably 16.8-17.2%, and even more preferably 17%.
[0024] In this invention, the mass percentage of Ni is preferably 5.5-6.5%, more preferably 5.8-6.2%, and even more preferably 6%.
[0025] In this invention, the mass percentage of Mn is preferably 3 to 5%, more preferably 3.5 to 4.5%, and even more preferably 4%.
[0026] In this invention, the mass percentage of Si is preferably 2.5 to 3.5%, more preferably 2.8 to 3.2%, and even more preferably 3%.
[0027] In this invention, the mass percentage of C is preferably 0.16 to 0.24%, more preferably 0.17 to 0.23%, and even more preferably 0.19 to 0.21%.
[0028] The present invention also provides a method for preparing the phase transformation-induced plasticity-resistant stainless steel, comprising the following steps: (1) The components are melted to obtain a billet; (2) The billet is subjected to heat treatment and recrystallization in sequence to obtain the phase transformation induced plasticity anti-oxidation stainless steel.
[0029] In this invention, the melting conditions in step (1) are argon atmosphere or vacuum.
[0030] In this invention, the temperature of the heat treatment in step (2) is preferably 850~1250℃, more preferably 900~1200℃, and even more preferably 1000~1100℃.
[0031] In this invention, the deformation of the hot working in step (2) is preferably ≥80%, more preferably ≥85%, and even more preferably ≥90%.
[0032] In this invention, the recrystallization temperature in step (2) is preferably 700~1300℃, more preferably 800~1200℃, and even more preferably 900~1100℃.
[0033] In this invention, the recrystallization time in step (2) is preferably ≥3 min, more preferably ≥20 min, and even more preferably ≥30 min.
[0034] In this invention, after recrystallization, the material is naturally cooled to room temperature to obtain an antioxidant stainless steel with phase transformation induced plasticity.
[0035] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0036] Example 1
[0037] In this embodiment, the chemical composition (mass percentage) of the phase transformation-induced plasticity-resistant oxidation stainless steel is Cr: 17%, Ni: 6%, Mn: 2%, Si: 3%, C: 0.2%, with the balance being Fe and unavoidable impurities; in this embodiment, W(Ni)eq is 11.21, satisfying the 10.3 standard. <W(Ni)eq<13.7。
[0038] The preparation method of phase transformation-induced plasticity antioxidant stainless steel is as follows: 1) The chemical composition and content of the oxidation-resistant stainless steel with phase transformation induced plasticity as described above are smelted in an electric arc melting furnace under an argon atmosphere, and after smelting is completed, it is cast into an alloy ingot; 2) The alloy ingot is hot rolled at 1100℃ with a deformation of 80%, and then recrystallized at 1000℃ for 30 min. After that, it is air-cooled to room temperature to obtain phase transformation induced plasticity anti-oxidation stainless steel.
[0039] The EBSD images of the phase transformation-induced plasticity anti-oxidation stainless steel before and after stretching in this embodiment are shown below. Figure 1 As shown, from Figure 1 It can be seen that the phase distribution diagram before fracture indicates that the recrystallized state is austenitic steel; the phase distribution diagram after fracture shows a large amount of martensite, indicating that the stainless steel underwent a phase transformation during the tensile process, that is, it has phase transformation induced plasticity.
[0040] Example 2
[0041] In this embodiment, the chemical composition (by mass percentage) of the phase transformation-induced plasticity-resistant oxidation stainless steel is Cr: 17%, Ni: 6%, Mn: 2%, Si: 2%, C: 0.2%, with the balance being Fe and unavoidable impurities; in this embodiment, W(Ni) eq The value is 11.76, which satisfies the requirement of 10.3. <W(Ni) eq <13.7.
[0042] The preparation method of phase transformation-induced plasticity antioxidant stainless steel is as follows: 1) The chemical composition and content of the oxidation-resistant stainless steel with phase transformation induced plasticity as described above are smelted in an electric arc melting furnace under an argon atmosphere, and after smelting is completed, it is cast into an alloy ingot; 2) The alloy ingot is hot rolled at 1100℃ with a deformation of 80%, and then recrystallized at 1000℃ for 30 min. After that, it is air-cooled to room temperature to obtain phase transformation induced plasticity anti-oxidation stainless steel.
[0043] Example 3
[0044] In this embodiment, the chemical composition (by mass percentage) of the phase transformation-induced plasticity-resistant oxidation stainless steel is Cr: 17%, Ni: 6%, Mn: 2%, Si: 4%, C: 0.2%, with the balance being Fe and unavoidable impurities; in this embodiment, W(Ni) eq The value is 10.44, which satisfies 10.3. <W(Ni) eq <13.7.
[0045] The preparation method of phase transformation-induced plasticity antioxidant stainless steel is as follows: 1) The chemical composition and content of the oxidation-resistant stainless steel with phase transformation induced plasticity as described above are smelted in an electric arc melting furnace under an argon atmosphere, and after smelting is completed, it is cast into an alloy ingot; 2) The alloy ingot is hot rolled at 1100℃ with a deformation of 80%, and then recrystallized at 1000℃ for 30 min. After that, it is air-cooled to room temperature to obtain phase transformation induced plasticity anti-oxidation stainless steel.
[0046] Example 4
[0047] In this embodiment, the chemical composition (by mass percentage) of the phase transformation-induced plasticity-resistant oxidation stainless steel is Cr: 17%, Ni: 6%, Mn: 6%, Si: 3%, C: 0.2%, with the balance being Fe and unavoidable impurities; in this embodiment, W(Ni) eq The value is 13.61, which satisfies 10.3. <W(Ni) eq <13.7.
[0048] The preparation method of phase transformation-induced plasticity antioxidant stainless steel is as follows: 1) The chemical composition and content of the oxidation-resistant stainless steel with phase transformation induced plasticity as described above are smelted in an electric arc melting furnace under an argon atmosphere, and after smelting is completed, it is cast into an alloy ingot; 2) The alloy ingot is hot rolled at 1100℃ with a deformation of 80%, and then recrystallized at 1000℃ for 30 min. After that, it is air-cooled to room temperature to obtain phase transformation induced plasticity anti-oxidation stainless steel.
[0049] Comparative Example 1
[0050] The only difference between this comparative example and Example 1 is that the mass percentage of Si is 6%; other chemical components and their contents, as well as the preparation conditions, remain unchanged; and W(Ni) is present in this comparative example. eq The value is 8.24, which does not meet the requirement of 10.3. <W(Ni) eq <13.7.
[0051] Comparative Example 2
[0052] The only difference between this comparative example and Example 1 is that the mass percentage of Si is 0%; other chemical components and their contents, as well as the preparation conditions, remain unchanged; and W(Ni) is present in this comparative example. eq The value is 12.20, which satisfies 10.3. <W(Ni) eq <13.7.
[0053] Comparative Example 3
[0054] The only difference between this comparative example and Example 1 is that the mass percentage of Ni is 3%; other chemical components and their contents, as well as the preparation conditions, remain unchanged; and W(Ni) in this comparative example... eqThe value is 8.21, which does not meet the requirement of 10.3. <W(Ni) eq <13.7.
[0055] Comparative Example 4
[0056] The only difference between this comparative example and Example 1 is that the mass percentage of Mn is 0%; other chemical components and their contents, as well as the preparation conditions, remain unchanged; and W(Ni) is present in this comparative example. eq The value is 10.01, which does not meet the requirement of 10.3. <W(Ni) eq <13.7.
[0057] Comparative Example 5
[0058] The only difference between this comparative example and Example 1 is that the mass percentage of Mn is 10%; other chemical components and their contents, as well as the preparation conditions, remain unchanged; and W(Ni) is present in this comparative example. eq The value is 16.01, which does not meet the requirement of 10.3. <W(Ni) eq <13.7.
[0059] Comparative Example 6
[0060] The only difference between this comparative example and Example 1 is that the mass percentage of C is 0%; other chemical components and their contents, as well as the preparation conditions, remain unchanged; and W(Ni) is present in this comparative example. eq The value is 9.27, which does not meet the requirement of 10.3. <W(Ni) eq <13.7.
[0061] Comparative Example 7
[0062] The only difference between this comparative example and Example 1 is that the mass percentage of C is 0.4%; other chemical components and their contents, as well as the preparation conditions, remain unchanged; and W(Ni) is present in this comparative example. eq The value is 13.15, which satisfies 10.3. <W(Ni) eq <13.7.
[0063] Comparative Example 8
[0064] Annealed 304 stainless steel purchased from the market had the following composition range (by mass percentage): Cr: 18~20%, Ni: 8~11%, Mn: 0~2%, Si: 0~0.75%, C: 0~0.08%. It was hot-rolled at 1100℃ with a deformation of 80%, then recrystallized at 1000℃ for 30 min, and subsequently air-cooled to room temperature to obtain Comparative Example 8.
[0065] Comparative Example 9
[0066] Annealed 316L stainless steel purchased from the market had the following composition range (by mass percentage): Cr: 16~18%, Ni: 10~15%, Mn: 0~2%, Si: 0~0.75%, C: 0~0.035%, Mo: 2-3%. It was hot-rolled at 1100℃ with a deformation of 80%, then recrystallized at 1000℃ for 30 min, and subsequently air-cooled to room temperature to obtain Comparative Example 9.
[0067] The mechanical properties of the examples and comparative examples were tested at room temperature, and the results are recorded in Table 1.
[0068] Table 1. Test results of room temperature mechanical properties of different stainless steels
[0069] The mechanical property test results of stainless steel in Examples 1, 8 and 9 at 400°C are shown in Table 2.
[0070] Table 2. Mechanical property test results of different stainless steels at 400℃
[0071] The mechanical properties of stainless steel in Examples 1, 8, and 9 at 600°C are shown in Table 3.
[0072] Table 3. Mechanical property test results of different stainless steels at 600℃
[0073] The mechanical property test results of stainless steel in Examples 1, 8 and 9 at 700°C are shown in Table 4.
[0074] Table 4. Test results of mechanical properties of different stainless steels at 700℃
[0075] The weight gain test results of stainless steels from Examples 1, 2, 8 and 9 after 96 hours of oxidation are shown in Table 5.
[0076] Table 5. Weight gain test results of different stainless steels after 96 hours of oxidation.
[0077] It can be seen from Tables 1 to 5 that Example 1 achieves a yield strength of 428 MPa, a tensile strength of 1324 MPa, and an elongation after fracture of 55% at room temperature; at 400℃ to 700℃, its yield strength, tensile strength and elongation after fracture are all superior to those of 304 and 316L stainless steels. Meanwhile, in terms of oxidation resistance, the oxidation weight gain per unit area at typical high-temperature service temperatures (800℃ and 900℃) is also far less than that of 304 and 316L stainless steels (a smaller oxidation weight gain per unit area indicates stronger oxidation resistance of the material).
[0078] The stainless steel of Comparative Example 1 has relatively high strength but extremely poor elongation (only 0.3%). This is because its Si content is excessively high, resulting in a nickel equivalent of only 8.24, which does not satisfy 10.3<W(Ni)eq<13.7, so that the alloy is composed of ferrite without austenite, and the alloy has relatively high strength but extremely poor plasticity.
[0079] Among the room-temperature properties of the stainless steel of Comparative Example 2, only the yield strength is relatively low, and the tensile strength and elongation are acceptable. However, due to the absence of Si, its oxidation weight gain per unit area at high temperature is higher than that of 304 and 316L, and its oxidation resistance is inferior to that of 304 and 316L.
[0080] Among the room-temperature properties of the stainless steel of Comparative Example 3, the yield strength and tensile strength are both acceptable. However, due to its excessively low Ni content, the nickel equivalent is relatively low, and the elongation is poor.
[0081] Among the room-temperature properties of the stainless steel of Comparative Example 4, the yield strength and tensile strength are both acceptable. However, due to its excessively low Mn content, the nickel equivalent is relatively low, and the elongation is poor.
[0082] Among the room-temperature properties of the stainless steel of Comparative Example 5, the yield strength and elongation are both acceptable. However, due to its excessively high Mn content, the nickel equivalent is relatively high, and the austenite is too stable, resulting in excessively low strength.
[0083] Among the room-temperature properties of the stainless steel of Comparative Example 6, the yield strength is acceptable. However, due to its excessively low C content, the nickel equivalent is relatively low, the austenite stability is poor, and the elongation is relatively low.
[0084] Among the room-temperature properties of the stainless steel of Comparative Example 7, the yield strength is acceptable. Although the nickel equivalent of this comparative example meets the requirement, due to its excessively high C content, carbonides are formed by combination with Cr, and these precipitated second phases will cause no necking to occur during the stretching process, leading to relatively low elongation.
[0085] Among the room-temperature properties of the stainless steel of Comparative Example 8, only the elongation is acceptable, the yield strength and tensile strength are both relatively low. At high temperature, the mechanical properties of this comparative example are all inferior to those of Example 1, and meanwhile the oxidation weight gain per unit area is significantly higher than that of Example 1, and the oxidation resistance is significantly worse than that of Example 1.
[0086] Of the stainless steel in Comparative Example 9, only the elongation was better than that of the embodiment in this patent at room temperature. The yield strength and tensile strength were both lower. At high temperatures, the mechanical properties of this comparative example were all inferior to those of Example 1. At the same time, the oxidation weight gain per unit area was significantly higher than that of Example 1, and the oxidation resistance was worse than that of Example 1.
[0087] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A phase transformation-induced plasticity-resistant oxidation-resistant stainless steel, characterized in that, The components comprise the following percentages by mass: Cr: 16~18%, Ni: 5~7%, Mn: 2~6%, Si: 2~4%, C: 0.17~0.25%, balance Fe; The above components satisfy the following relationship: 10.3 <W(Ni)eq<13.7; in: W(Ni)eq=W(Ni)+0.6W(Mn)+0.18W(Cr)+9.69W(C)-0.11W(Si) 2 ; W(X) represents the mass percentage of element X × 100, and W(Ni)eq is the nickel equivalent.
2. The method for preparing the phase transformation-induced plasticity-resistant antioxidant stainless steel according to claim 1, characterized in that, Includes the following steps: (1) The components are melted to obtain a billet; (2) The billet is subjected to heat treatment and recrystallization in sequence to obtain the phase transformation induced plasticity anti-oxidation stainless steel.
3. The method for preparing phase transformation-induced plasticity antioxidant stainless steel as described in claim 2, characterized in that, The melting conditions in step (1) are argon atmosphere or vacuum.
4. The method for preparing phase transformation-induced plasticity antioxidant stainless steel as described in claim 3, characterized in that, The temperature of the heat treatment in step (2) is 850~1250℃.
5. The method for preparing phase transformation-induced plasticity antioxidant stainless steel as described in claim 4, characterized in that, The deformation of the hot working in step (2) is ≥80%.
6. The method for preparing phase transformation-induced plasticity antioxidant stainless steel as described in claim 5, characterized in that, The recrystallization temperature in step (2) is 700~1300℃.
7. The method for preparing phase transformation-induced plasticity antioxidant stainless steel as described in claim 6, characterized in that, The recrystallization time in step (2) is ≥3 min.
Citation Information
Patent Citations
800-1,600 MPa grade high strength austenitic stainless steel, manufacturing method and warm forming method
CN105200340A
Stainless steel suitable for high-pressure hydrogen environment
CN119932446A
Austenite stainless steel sheet and method for producing same
CN102639742A
High strength and high ductility stainless steel
JP1992063247A